PENGARUH KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL, KEPEMILIKAN ASING, KEPEMILIKAN INDIVIDU, KEBIJAKAN HUTANG DAN DIVIDEN TAHUN SEBELUMNYA BERPENGARUH TERHADAP KEBIJAKAN DIVIDEN - Melita, Willi; Rokhmawati, Andewi (Jurnal Tepak Manajemen Bisnis, 2017)
This study to aims to determine the effect of managerial ownership, institutional ownership, foreign ownership, individual ownership, debt policy and dividend policy of the previous year the dividend on the companyâs food and beverage manufacturers do sectors listed in Indonesia Stock Exchange in 2010 to 2015. To achieve the goal the research conducted by taking a sample of 14 companies manufacturers do food and beverage sector listed in In donesia Stock Exchange in 2010 to 2015. The analysis method used is multiple linear regression model. The results showed that managerial ownership, institutional ownership, foreign ownership, individual ownership, debt policy and dividend policy of the previous year jointly significant effect on dividend policy. Partially managerial ownership and debt policy does not have a negative significant effect on dividend policy, foreign ownership does not have a positive significant effect on dividend policy, individual ownership and the previous yearâs dividend partially positive significant effect on dividend policy.